Co-Immobilized Capillary Enzyme Reactor Based on Beta-Secretase1 and Acetylcholinesterase: A Model for Dual-Ligand Screening - Vilela, Adriana Ferreira Lopes; Narciso dos Reis, Vitor Eduardo; Cardoso, Carmen Lúcia (Frontiers in Chemistry, 2021)
We have developed a dual enzymatic system assay involving liquid chromatography-mass spectrometry (LC–MS) to screen AChE and BACE1 ligands. A fused silica capillary (30 cm x 0.1 mm i.d. x 0.362 mm e.d.) was used as solid support. The co-immobilization procedure encompassed two steps and random immobilization. The resulting huAChE+BACE1-ICER/MS was characterized by using acetylcholine (ACh) and JMV2236 as substrates. The best conditions for the dual enzymatic system assay were evaluated and compared to the conditions of the individual enzymatic system assays. Analysis was performed in series for each enzyme. The kinetic parameters (KMapp) and inhibition assays were evaluated. To validate the system, galantamine and a β-secretase inhibitor were employed as standard inhibitors, which confirmed that the developed screening assay was able to identify reference ligands and to provide quantitative parameters. The combination of these two enzymes in a single on-line system allowed possible multi-target inhibitors to be screened and identified. The innovative huAChE+BACE1-ICER/MS dual enzymatic system reported herein proved to be a reliable tool to identify and to characterize hit ligands for AChE and BACE1 in an enzymatic competitive environment. This innovative system assay involved lower costs; measured the product from enzymatic hydrolysis directly by MS; enabled immediate recovery of the enzymatic activity; showed specificity, selectivity, and sensitivity; and mimicked the cellular process.